The awareness of the primary school teachers in Dungun towards the application of Aslah (personal loan) scheme in Bank Rakyat / Nur Hayatie Ismail - Ismail, Nur Hayatie (2008)
This study examines the awareness of primary school teachers in Dungun towards personal loan (Aslah) scheme offered by Bank Rakyat. The dependent variable in this study is the awareness of primary school teachers in Dungun towards personal loan (Aslah) scheme offered by Bank Rakyat while the independent variables are knowledge, promotion and attitude. The objective of this study is to know the level of awareness among primary school teachers in Dungun towards personal loan (Aslah) offered by Bank Rakyat. All of the information needed have been gathered by using primary and secondary data. In order to collect primary data, the researcher used the questionnaire. The researcher also used references such as journal, books and on line internet to get the information. Data were collecting from 100 respondents from primary school teachers in Dungun. Here, the researcher used the convenience sampling. This study used such as the reliability analysis in scale, Pearson correlation, frequency and cross tabulation. In the findings, it can be concluded that the variables in this study are considered good because the Cronbach’s Alpha for both independent (knowledge, promotion and attitude) and dependent (awareness) are over 0.80. The result is 0.845. From the finding and conclusion, the researcher recommended that the Bank Rakyat must do something to increase the promotion of Islamic Banking product generally and Aslah especially. The Bank Rakyat also can be increased the features of Aslah scheme to facilitate the installment payment, this action can be attract the public or individual to practice of Islamic Banking products as an alternative in their life. Indirectly, it will increase the awareness among them.